TCM family movie night menus : recipes & films for unforgettable times together - Maltin, Leonard; Maltin, Jessie, 1986- (Running Press, 2026)
"A family-themed follow-up to TCM's Movie Night Menus with a celebrity duo of authors already associated with movie entertainment, beloved film critic Leonard Maltin and his daughter and podcast cohost Jessie Maltin, this is the essential guide to family-friendly film recommendations paired with recipes to take family fun time to the next level"-- Provided by publisher.